2001
DOI: 10.1007/s002530000566
|View full text |Cite
|
Sign up to set email alerts
|

High-rate 3-methylcatechol production in Pseudomonas putida strains by means of a novel expression system

Abstract: The bioconversion of toluene into 3-methylcatechol was studied as a model system for the production of valuable 3-substituted catechols in general. For this purpose, an improved microbial system for the production of 3-methylcatechol was obtained. Pseudomonas putida strains containing the todC1C2BAD genes involved in the conversion of toluene into 3-methylcatechol were used as hosts for introducing extra copies of these genes by means of a novel integrative expression system. A construct was made containing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 27 publications
3
35
0
Order By: Relevance
“…5B). This is in agreement with previous reports that 3MC is unstable in aqueous phase at a relatively basic pH and either undergoes oxidation or chemical degradation (Husken et al, 2001(Husken et al, , 2002 or polymerization to form o-benzoquinone (Borraccino et al, 2001;Hüsken et al, 2001;Mijangos et al, 2006;Wery et al, 2000), while it was more stable in organic phase (Fig. 5B).…”
Section: Fed-batch Production Of 3mc In a 2-l Bioreactorsupporting
confidence: 83%
See 3 more Smart Citations
“…5B). This is in agreement with previous reports that 3MC is unstable in aqueous phase at a relatively basic pH and either undergoes oxidation or chemical degradation (Husken et al, 2001(Husken et al, , 2002 or polymerization to form o-benzoquinone (Borraccino et al, 2001;Hüsken et al, 2001;Mijangos et al, 2006;Wery et al, 2000), while it was more stable in organic phase (Fig. 5B).…”
Section: Fed-batch Production Of 3mc In a 2-l Bioreactorsupporting
confidence: 83%
“…It was previously reported that OST P. putida could tolerate 3MC up to 5.5 mM (Hüsken et al, 2001), while this study showed that the P. putida T57 wild-type strain as well as the TODE1 mutant strain could tolerate up to 7 mM 3MC when tested under growing-cell conditions. In this study, as the production goal was to produce 3MC at higher concentrations, the use of a high-density OST resting-cell-based bioproduction was employed instead of a growing-cell based one.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…Alternatively, solvent-tolerant strains can be used to express the enzyme to improve biocatalyst stability in the presence of solvents that are generally toxic to microorganisms (14). Solvent-tolerant strains have been used previously for production of toxic products, such as 3-methyl catechol, in the presence of toxic organic solvents (14,15,32). More work is being done to improve 1-naphthol production using solvent-tolerant strains and biphasic systems.…”
Section: Discussionmentioning
confidence: 99%